Analysis and variable step control of a bidirectional complementary-type inchworm actuator. (9th March 2021) - Sun, Tiantian; Wang, Yue; Yan, Peng
Abstract: To meet the demands of high speed and large loading capacity in various nanopositioning applications, a voltage sequence based step analysis and the corresponding variable step control strategy are explored for a bidirectional complementary-type inchworm actuator. Specifically, the bidirectional variable step motion can be achieved without significant drop of the loading capacity by controlling the two-channel input voltage sequences, where the variable speed motions can help to achieve more rapid nano-positioning tasks. In particular, we introduce the voltage sequences in the modelling of the step length and the total clamping force for the purpose of achieving controllable bidirectional motion with large loading capacity. Real time control experiments are comprehensively conducted, which demonstrates a bidirectional variable step motion range of ±22 µ m is achieved by controlling two-channel input signals. In addition, the actuator with the proposed method has an adjustable total clamping force capable of improving the motion stability and loading capacity in variable step motion, which are favourable to various engineering applications in high speed nanopositioning areas.